The French Cultural Strategy and the Japanese Paradigm: How to Seduce in International Relations in the 21st Century? - Fregonese, Pierre-William; Sakai, Kazunari (Alternative francophone, 2021)
France used to have one of the most powerful cultural diplomacy: it needs nowadays to modernize its strategy to hold on to its international position. France has a long history of foreign cultural policy and is one of the few countries that have placed great emphasis on fostering its culture abroad. However, the French position is currently being challenged by emerging international rivalries. Establishing a cultural strategy in the 21st century requires not only a consistent approach between the projection of an elite culture and of a pop culture, but also a joint action between public and private players. Japan could be a model, even a paradigm for France and its cultural action abroad, as well as an ally through a cultural alliance.